Local Food Product Branding through Catalog Photos and Social Media Management Assistance - Rachmawati, Aulia; Febriana, Poppy; Aesthetika, Nur Maghfirah; Rochmania, Ainur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: The use of social media can also help complete work, especially advancing micro, small, and medium enterprises (MSMEs) in the Sidoarjo area. This community service activity is carried out to promote local products and also increase the knowledge and skills of micro, small, and medium enterprises (MSMEs) so that they are able to increase product sales and marketing using social media platforms, especially Instagram accounts. Methodology: This activity goes through three stages: observation carried out with discussion, preparation carried out by providing materials, and implementation carried out with assistance with product photos and social media management. Results: The result of this service is to provide benefits and knowledge regarding the importance of social media and product photos in increasing sales for MSMEs. Applications/Originality/Value: What was obtained after carrying out this activity was that Kupang Jaya MSMEs and Sustainable Kitchens had catalog photos and social media as a forum for promoting sales.